ANALISIS GAYA BELAJAR SISWA SEKOLAH DASAR NEGERI 2 PRINGSEWU SELATAN PADA PEMBELAJARAN BAHASA INDONESIA DENGAN MEDIA VISUAL DAN AUDITORY - Puspita, Dian; Anggraeni, Leni (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
Analysis of learning styles can help educators to develop learning strategies that are more effective and in accordance with the needs of students. Relevant surveys and questionnaires to identify student learning styles. Questions in the questionnaire can relate to students' learning preferences, for example, whether they prefer to learn through reading, listening, or participating in physical activities. in-class observation to see how students respond to various teaching methods. Notice if they are more active when looking at pictures, listening to stories, or interacting directly with teachers and classmates. Identify the dominant learning style that is owned by the majority of students. Learning styles are generally divided into three categories: visual (learning through pictures and diagrams), auditory (learning through hearing and oral discussion), and kinesthetic (learning through physical movement and direct interaction). Student involvement always prioritizes student interaction and involvement in learning. By involving students actively, they will be more interested and eager to learn. A diverse and inclusive learning approach will be more effective in achieving successful learning for all students in the class.